Asynchronous Digital-Based Learning Transformation of Speaking Skill Through Instagram - Anggi Novitasari; Primardiana Hermilia Wijayati; Roekhan Roekhan (Universitas Negeri Malang, 2020)
This article is the result of a research related to Asynchronous digital-based learning in speaking skill through instagram. This study aims to determine the transformation of Asynchronous digital-based learning and to analyze the students' speaking skill using the assessment rubric that has been designed. The data were collected through oral practice in the form of videos related to the theme Freizeitbeschäftigung / Hobby. Each student was asked to upload a 2-3 minute video and comment on two videos of other students. The results of this study indicated that the assessment rubric covered the fulfillment of tasks and pronunciation. All the given assignment points were fulfilled quite well, although there were six students who still made grammatical errors. The pronunciation ability of seven students was very good, while the other seven students were still influenced by Indonesian accent. Students' comments regarding other students’ videos were varied and positive. Students gave supportive comments to motivate each other in doing their work and they did not have any difficulties in using instagram. Keywords: Asynchronous, German language learning, instagram, speaking skill